Cognitive and motivational variables as predictors of performance in game actions in young volleyball players - Fernando Claver Rabaz; Ruth Jiménez Castuera; Manuel Conejero Suárez; Luis García González; Maria Perla Moreno Arroyo (European Journal of Human Movement, 2015)
The main aim of this research was to analyze the level of prediction of different motivational and cognitive variables on performance in game actions, considering the ranking obtained by the teams at the end of the season. The study sample was composed of 134 Under-16 (male and female) volleyball players (M: 14.82; SD: .89) who compete in a regional league (Extremadura), and were divided into four groups according to the classification. The study variables were: motivational (basic psychological needs and motivation), cognitive (procedural knowledge and decision-making), and performance in game actions. The data research techniques used involved three questionnaires: Spanish version of Sport Motivation Scale by Núñez et al., (2006), Motivational Mediators Scale by González-Cutre et al. (2007) and Procedural Knowledge Questionnaire (Moreno et al., 2013); the systematic observation of game actions for decision-making (GPAI, Oslin et. al, 1998) and performance analysis (FIVB, Coleman, 1975). The results showed that cognitive and motivational variables acted as predictors of performance in players from top teams (1st and 2nd). In the other teams (from 3rd to 8th), only cognitive variables acted as predictors of players’ performance. The Self-Determination Theory and the Theory of Information Processing in Sports were used as theoretical framework underpinning the study. These results are discussed on the basis of works that highlight the need and importance of a joint action by the coach on those variables that determine players’ performance.